Pesticides Residues in Grains Marketed In Brazil - Ana Carolina Pereira Paiva; Kassio Ferreira Mendes (Pesticides in Agriculture and Environment, 2021)
Brazil is a world reference in agricultural production. In the grain sector, the country reached a record in the 2019/2020 harvest, with production above 257 million tons, and the forecast of “Companhia Nacional de Abastecimento” (CONAB) is new record in the 2020/2021 crop (CONAB, 2020 and 2021b). However, with increased productivity and growing dietary needs, pesticide use has increased. Herbicides, fungicides and insecticides constitute the classes of pesticides with the highest consumption and economic importance (PELAEZ et al., 2016). In Brazil, one of the largest pesticide consumers in the world, the use and marketing of these products has maintained high rates over the last few years. The “Sindicato Nacional da Indústria de Produtos para Defesa Vegetal” (SINDIVEG) points out that more than 600,000 tons of formulated products were marketed in the country in 2019. It is important that the use of pesticides is made following the recommendation standards, in order to avoid contamination, both of the grains, as well as of the environment and the applicator. However, studies indicate the presence of residues of various pesticides in food matrices, which is a source of concern (ABRASCO, 2015; ANVISA, 2016). These contaminations occur due to several factors such as drift, use of doses above the recommended, non-respect of the grace period, use of products not registered for the crop or non-observation of the time of application (AZEVEDO and FREIRE, 2006; ABRASCO, 2015).